Implementation of Lactation Management for the Success of the Breastfeeding Process for Post Partum Mothers in the Independent Practice of Midwife Veronika, Batam City - Andi Sri Astuti; Aminah Aatinaa Adhyatma; Indah Mastikana (Universitas Islam Lamongan, 2021)
Mother's milk (ASI) is a very special food source and the only food needed by babies. Mother's role is to provide breast milk as a form of child's exclusive right for six full months without any other food and drink, continued until the child is 2 years old with complementary foods. Breastfeeding is the best method for maternal health and healthy baby growth and development as the nation's next generation of quality. Globally, the exclusive breastfeeding rate for infants under six months of age is 40%. Only 23 countries achieve at least 60% of infants less than six months who are exclusively breastfed. The general purpose of this study was to describe the implementation of lactation management for the success of breastfeeding in post partum mothers. Meanwhile, the specific objective of this study was to implement lactation management for Mrs. “D” so that she could breastfeed immediately after giving birth. This research method uses a descriptive research design. Descriptive research is a research method that is carried out with the main aim of making a picture or description of a situation objectively. The results of midwifery care implementing the implementation of lactation management from the 3rd trimester of pregnancy until the puerperium have proven successful in the breastfeeding process with family support, especially the support of the husband and health workers, as a determining factor for the success of care and success in exclusive breastfeeding. In conclusion, during monitoring there were no complications, complications and danger signs in the baby, the baby was able to breastfeed well.